Pengembangan Pemasaran UMKM pada Usaha Bawang Goreng di Pasar Inpes Kota Palu - Novry Dwiyanti; Andi Nurul Istiqamah; Jesika Julianti Natalia Kamasi; Rima Amanda Azzahra; Nuraisyah Nuraisyah; Andi Maman Firmansyah; Meldi Amijaya (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The aim of this research is to analyze and develop an effective marketing strategy for the fried onion business at the Impres Market, Palu City. By understanding the potential and challenges faced by UMKM players. This research uses a descriptive method with a qualitative approach. Data collection techniques in this research are library research, observation techniques, and interview techniques. The data analysis technique that the author uses in this research is an interactive model data analysis tool from Milles, Huberman and Saldana. The implementation of the 4P marketing mix (Product, Price, Place, Promotion) is very important to increase the competitiveness of the fried onion UMKM business at the Palu City Impres Market. Focusing on product quality, setting reasonable prices, utilizing e-commerce platforms, and promoting via social media can expand the market and attract more consumers. With this strategy, the fried onion business can develop, increase turnover and strengthen its position in the market Keywords: Fried Onions; Marketing;UMKM